Enhanced identification of maternal hepatitis C virus infection using existing public health surveillance systems. Issue 4 (4th July 2018) - Gowda, Charitha; Kennedy, Samuel; Glover, Catherine; Prasad, Mona R.; Wang, Ling; Honegger, Jonathan R.
Abstract: Background: Hepatitis C virus (HCV) infection is under‐recognized among US adults and children. Prenatal HCV screening may help close the diagnosis gap among women while also identifying at‐risk infants. Current surveillance efforts for maternal HCV rely primarily on birth certificate data. We sought a more accurate assessment of HCV prevalence among pregnant women in Ohio by combining existing public health surveillance data. Methods: Vital Statistics (VS) birth certificate data and Ohio Disease Reporting System (ODRS) HCV case data, both available through the Ohio Department of Health, were linked to determine rates of past or present HCV infection among women giving birth from 2012 to 2015 in Ohio, overall and by county. Among women with available test results, the proportion with present HCV infection indicated by detectable viraemia during pregnancy was calculated. Results: Birth certificate data identified 4695 deliveries to women with past/present HCV infection during the study period. Linkage to ODRS revealed an additional 1778 deliveries to women with past/present infection, including 355 with confirmed viraemia during pregnancy. The prevalence of past/present HCV among pregnant women in Ohio rose from 0.82% in 2012 to 1.54% in 2015. Conclusions: Maternal HCV infection is under‐recognized and increasing in prevalence. Current case identification processes are inadequate in pregnancy, even among women with prior positive HCV testing. Alternative approaches, including enhanced risk factor‐based screening or universal prenatal screening in high prevalence settings, are needed to improve rates of HCV recognition among reproductive‐aged women and newborns at risk of vertical transmission.